VIDEO-BASED REFLECTION FOR TEACHERS' PROFESSIONALISM IMPROVEMENT: A Case of Junior High School In-service Teachers in Bandung - Erni Hamidah, - (2019)
Doing reflective practice is a hallmark of teachers' professionalism in the world. One means to achieve it is through structuring the reflective practice via technology. Unfortunately, it was found rare in Indonesian classroom practice. The central issue of this study was to find out whether the practice of video-based reflection lead in-service teachers to improving their teaching practice and to uncover benefits and drawbacks of video-based reflection within Indonesian in-service teachers' professional development. Qualitative case study design was used to illuminate and declare every details of them over triangulating through three kinds of data: reflective writings, semi structured interview and field notes from video observations. It was found that video-based reflection helped teachers to notice actual teaching and learning events which actually need their immediate "helps". It also grants the teachers to recognize and evaluate their own aspect of teaching and also allowed the teachers to plan precise "response" to their subsequent lesson. The drawbacks of video-based reflection was detected on its technical constraints: condition of the device, teachers' familiarity to the process, and involvement of other party who took part as the camerapersons. Time of the process conduction was also contributed as one of its drawbacks. It suggests to result in earnest and worthy circumstances of classroom practice that should be internalized into the teachers' self-praxis to fulfill the advisability principle as a professional teacher and accompanied by device compliance to give optimum facilitation and accommodation for teacher professional development.; Melakukan tindakan reflektif adalah ciri khas profesionalisme guru di dunia. Salah satu cara untuk mencapainya adalah melalui menjembatani praktik tindakan reflektif melalui teknologi. Sayangnya, hal ini jarang ditemukan dalam praktikpembelajaran di ruang-ruang kelas di Indonesia. Tujuan utama dari penelitian ini adalah untuk mengetahui apakah praktik refleksi berbasis video dapat menuntun guru untuk meningkatkan praktik mengajar mereka dan juga untuk mengungkap manfaat dan kelemahan refleksi berbasis video dalam pengembangan profesional guru (dalam jabatan) di Indonesia. DEsain penelitian yang digunakan adalah studi kasus guna untuk menyatakan dan membuat setiap detailnya terang benderang melalui kegiatan triangulasi melalui tiga jenis data: tulisan reflektif, wawancara semi terstruktur dan catatan lapangan dari pengamatan video. Berdasarkan penelitian ini, ditemukan bahwa refleksi berbasis video mendorong guru untuk memperhatikan kegiatan belajar mengajar yang sebenarnya membutuhkan "bantuan" langsung mereka. Para guru juga terbantu untuk mengenali dan mengevaluasi aspek pengajaran mereka sendiri dan memungkinkan mereka untuk merencanakan "respons" yang tepat untuk pelajaran mereka berikutnya. Kelemahan dari refleksi berbasis video terdeteksi terletak pada kendala teknis: kondisi perangkat, keakraban guru dengan proses, dan keterlibatan pihak lain yang mengambil bagian sebagai juru kamera. Waktu proses konduksi juga berkontribusi sebagai salah satu kekurangannya. Adalah penting untuk menginternalisasi praktik semacam ini menjadi bagian dari kegiatan profesional guru demi pemenuhan kelayakan sebagai kalangan profesional sehingga tidak berlebihan bila para guru disarankan untuk memfasilitasi dan mengakomodasi diri dalam rangka pengembangan professional guru yang lebih optimal.